Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 121500 by bramlexs22 last updated on 08/Nov/20

 (1) ∫ (dx/(x^4 +2x^2 +9)) ?  (2) arc tan ((x/3))−arc tan ((x/3))= arc tan ((1/5))

(1)dxx4+2x2+9?(2)arctan(x3)arctan(x3)=arctan(15)

Commented by benjo_mathlover last updated on 08/Nov/20

i think it should be   (2) tan^(−1) ((x/3))−tan^(−1) ((x/2))= tan^(−1) ((1/5))  let x = 6ψ ⇒ tan^(−1) (2ψ)−tan^(−1) (3ψ)=tan^(−1) ((1/5))  ⇔ ((2ψ−3ψ)/(1+6ψ^2 )) = (1/5) ; 6ψ^2 +5ψ+1=0  (2ψ+1)(3ψ+1)=0 → { (((1/6)x=−(1/2);x =−3)),(((1/6)x=−(1/3); x=−2)) :}

ithinkitshouldbe(2)tan1(x3)tan1(x2)=tan1(15)letx=6ψtan1(2ψ)tan1(3ψ)=tan1(15)2ψ3ψ1+6ψ2=15;6ψ2+5ψ+1=0(2ψ+1)(3ψ+1)=0{16x=12;x=316x=13;x=2

Answered by Ar Brandon last updated on 09/Nov/20

1\I=∫(dx/(x^4 +2x^2 +9))=(1/6)∫(((x^2 +3)−(x^2 −3))/(x^4 +2x^2 +9))dx     6I=∫((x^2 +3)/(x^4 +2x^2 +9))dx−∫((x^2 −3)/(x^4 +2x^2 +9))dx           =∫((1+(3/x^2 ))/(x^2 +2+(9/x^2 )))dx−∫((1−(3/x^2 ))/(x^2 +2+(9/x^2 )))dx            =∫((1+(3/x^2 ))/((x−(3/x))^2 +8))dx−∫((1−(3/x^2 ))/((x+(3/x))^2 −4))dx             =∫(du/(u^2 +8))−∫(dv/(v^2 −4))=(1/(2(√2)))Arctan((u/(2(√2))))+(1/2)Arctanh((v/2))+C

1I=dxx4+2x2+9=16(x2+3)(x23)x4+2x2+9dx6I=x2+3x4+2x2+9dxx23x4+2x2+9dx=1+3x2x2+2+9x2dx13x2x2+2+9x2dx=1+3x2(x3x)2+8dx13x2(x+3x)24dx=duu2+8dvv24=122Arctan(u22)+12Arctanh(v2)+C

Answered by MJS_new last updated on 09/Nov/20

∫(dx/(x^4 +2x^2 +9))=∫(dx/((x^2 −2x+3)(x^2 +2x+3)))=  =(1/(12))∫(((x+2)/(x^2 +2x+3))−((x−2)/(x^2 −2x+3)))dx=  =(1/(12))∫(dx/(x^2 +2x+3))+(1/(24))∫((2x+2)/(x^2 +2x+3))dx+  +(1/(12))∫(dx/(x^2 −2x+3))−(1/(24))∫((2x−2)/(x^2 −2x+3))dx=  =((√2)/(24))arctan (((√2)(x+1))/2) +(1/(24))ln (x^2 +2x+3) +  +((√2)/(24))arctan (((√2)(x−1))/2) −(1/(24))ln (x^2 −2x+3) +C

dxx4+2x2+9=dx(x22x+3)(x2+2x+3)==112(x+2x2+2x+3x2x22x+3)dx==112dxx2+2x+3+1242x+2x2+2x+3dx++112dxx22x+31242x2x22x+3dx==224arctan2(x+1)2+124ln(x2+2x+3)++224arctan2(x1)2124ln(x22x+3)+C

Answered by TANMAY PANACEA last updated on 09/Nov/20

1)∫((1/x^2 )/(x^2 +(9/x^2 )+2))dx  (1/6)∫(((1+(3/x^2 ))−(1−(3/x^2 )))/(x^2 +(9/x^2 )+2))dx  (1/6)∫((d(x−(3/x)))/((x−(3/(x )))^2 +8)) −(1/6)∫((d(x+(3/x)))/((x+(3/x))^2 −4))  (1/6)×(1/( (√8)))tan^(−1) (((x−(3/x))/( (√8))))−(1/6)×(1/(2×2))ln(((x−(3/x)−2)/(x−(3/x)+2)))+c

1)1x2x2+9x2+2dx16(1+3x2)(13x2)x2+9x2+2dx16d(x3x)(x3x)2+816d(x+3x)(x+3x)2416×18tan1(x3x8)16×12×2ln(x3x2x3x+2)+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com